Slavoj Žižek - Myers, Tony, 1969- (Routledge critical thinkers, 2003)
"Slavoj Zizek is no ordinary philosopher. Approaching critical theory and psychoanalysis in a recklessly entertaining fashion, Zizek's critical eye alights upon a bewildering and exhilarating range of subjects, from the political apathy of contemporary life, to a joke about the man who thinks he's a chicken, from the ethicial heroism of Keanu Reeves in speed, to what toilet designs reveal about the national psyche. Tony Myers provides a clear and engaging guide to Zizek's key ideas, explaining the main influences on Zizek's thought, most crucially his engagement with Lacanian psychoanalysis, using examples drawn from popular culture and everyday life." "Slavoj Zizek is essential reading for anyone wanting to understand the thought of the critic whom Terry Eagleton has described as "the most formidably brilliant exponent of psychoanalysis, indeed of cultural theory in general, to have emerged in Europe for some decades.""--BOOK JACKET.